Analisis Jumlah Kantor dan Pembiayaan Bank Syariah Terhadap Pertumbuhan Ekonomi di Indonesia - HASIM, CDEFGHI; junaidi, junaidi; sultan, sultan (Akuisisi : Jurnal Akuntansi, 2023)
As intermediary institutions, Islamic banks are Islamic financial institutions that play a major role in the pace of development and economic growth in Indonesia. that can be used by all members of society. Not only the Muslim community, but also in its operational activities besides being oriented towards sound business ethics (according to sharia principles) it is also based on the values of expediency and justice. This study examines the effect of the number of Islamic bank offices, and the amount of financing on economic growth in Indonesia. The population in this study are all Islamic banks for 2009 -2022 in the form of quarterly financial reports and those obtained from the financial services authority (OJK). Data analysis used is by using the panel vector eros correction model (VECM). This study shows that financing affects economic growth, and at the same time, the number of offices does not affect economic growth.